2021
DOI: 10.1080/13697137.2021.1951204
|View full text |Cite
|
Sign up to set email alerts
|

A pas de deux of osteoporosis and sarcopenia: osteosarcopenia

Abstract: The musculoskeletal conditions osteoporosis and sarcopenia are highly prevalent in older adults. Osteoporosis is characterized by low bone mass and microarchitectural deterioration of bone, whereas sarcopenia is identified by the loss of muscle strength, function and mass. Osteoporosis represents a major health problem contributing to millions of fractures worldwide on an annual basis, whereas sarcopenia is associated with a range of adverse physical and metabolic outcomes. They both affect physical and social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 117 publications
(130 reference statements)
0
10
0
Order By: Relevance
“…Genetic, mechanical, and endocrine factors may explain the age-related association between muscle and bone loss [37]. There is accumulating evidence that other localized and systemic factors are involved, including mesenchymal stem cells residing in connective tissue (muscle, bone, and fat), myokines and osteokines (molecules released from muscle and bone cells, respectively), inflamm-ageing, and fat infiltration [38]. These pathophysiological findings are common to both sarcopenia and osteoporosis, thus suggesting that the two are closely linked [39].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic, mechanical, and endocrine factors may explain the age-related association between muscle and bone loss [37]. There is accumulating evidence that other localized and systemic factors are involved, including mesenchymal stem cells residing in connective tissue (muscle, bone, and fat), myokines and osteokines (molecules released from muscle and bone cells, respectively), inflamm-ageing, and fat infiltration [38]. These pathophysiological findings are common to both sarcopenia and osteoporosis, thus suggesting that the two are closely linked [39].…”
Section: Discussionmentioning
confidence: 99%
“…Before progressing too far via evolution, exposure to GRFs by the initial organisms that ventured out of the water onto land would require adaptation not only of the bony skeleton and muscles, but also the regulatory elements of bones and muscles, as well as the supporting tissues required for mobility via articulating joints (i.e., ligaments, tendons, cartilage, menisci, synovium, and joint capsules) and a segmented spine. Of particular importance would have been the evolution of the “bone–muscle units” with extensive crosstalk [ 23 , 156 , 157 ], as well as the nerves and vasculature that regulate such tissues. While the vasculature would have been subjected to shear while living and evolving in the oceans and lakes, with the advent of walking on land the vasculature of the lower extremities would also have been exposed to GRFs along with the bones and muscles, and as such, would be required to adapt to such impact loading without initiating damage.…”
Section: Are Responses To Grfs Mechanistically Unique Due To Exposure...mentioning
confidence: 99%
“…However, such deformation loading may be more influenced by muscles and local environments than GRFs generated at the foot. In the tibia, calf muscles can exert significant loading on the bones to result in changes (part of the muscle–bone unit) [ 23 , 156 , 162 ]. Whether such muscle–bone interactions in response to GRFs persist above the knee remains to be determined.…”
Section: Are Responses To Grfs Mechanistically Unique Due To Exposure...mentioning
confidence: 99%
“…Some studies have also shown that bone loss is accelerated in patients with osteoporosis who develop sarcopenia, but the mechanism is unclear. [ 3 ] During growth and development, bones and muscles are influenced by many of the same factors and can influence each other. [ 4 ] Activity can promote the growth of muscle tissue, and the stimulation of external stress on the bone can also promote the growth and development of bone tissue.…”
Section: Introductionmentioning
confidence: 99%